Public Private Partnership in Tourism: Build Up a Digitalization Financial Management Model - Damas Dwi Anggoro; Hanifa Maulani Ramadhan; Rispa Ngindana (Policy & Governance Review, 2022)
The limitation of the government's budget is sometimes unable to accommodate the overall demand of infrastructure development which requires a large investment. Yet, the Public-Private Partnership (PPP) has been recognized as one of promising tool to build cross-sectoral collaboration to support insfrastructure development within the last few decades. Indonesia has several frameworks of PPP cooperation to accomplish development goals as stated in The Minister of Development Planning Act No. 4/2015. Despite several frameworks provided by the government. This research uses a qualitative approach which is conducted through interviews with several key informants as well as relevant observation. The result of this research shows that PPP has been fully implemented in Lamongan. Through the attractiveness of marine tourism, the local government of Lamongan Regency is looking for investment in tourism development through PPP. Wisata Bahari Lamongan and Mazola (Maharani Zoo Lamongan) are two tourist attractions that implement a private partnership funding system with the Build Operate Transfer (BOT) scheme. This mechanism is used sustainably as an operational effort for Lamongan and Mazola Marine Tourism (Maharani Zoo Lamongan). Revenue from tourism is included in the Regional Original Revenue (PAD) and as private sector income in this project.